2013
DOI: 10.1007/s10565-013-9254-1
|View full text |Cite
|
Sign up to set email alerts
|

Benzo-[a]-pyrene induces FAK activation and cell migration in MDA-MB-231 breast cancer cells

Abstract: Benzo-[a]-pyrene (B[a]P) is a family member of polycyclic aromatic hydrocarbons and a widespread environmental pollutant. It is a mammary carcinogen in rodents and contributes to the development of human breast cancer. However, the signal transduction pathways induced by B[a]P and its role in breast cancer progression have not been studied in detail. Here, we demonstrate that B[a]P induces cell migration through a lipoxygenase- and Src-dependent pathway, as well as the activation of focal adhesion kinase, Src,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…PAHs (Lecureur et al, 2005;Castillo-Sanchez et al, 2013). This may be consistent with the hypothesis that DEPe only transiently induced FAK and ERK activity in BEAS-2B cells, as soon as a sufficient level of DEPe-mediated CD98hc induction was reached.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…PAHs (Lecureur et al, 2005;Castillo-Sanchez et al, 2013). This may be consistent with the hypothesis that DEPe only transiently induced FAK and ERK activity in BEAS-2B cells, as soon as a sufficient level of DEPe-mediated CD98hc induction was reached.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…It has further been observed that PTEN has the potential to regulate the invasive behavior of tumor cells by affecting the expression and phosphorylation level of focal adhesion kinase (FAK) (27). The activation of FAK promotes the proliferation and invasion of tumor cells, which are crucial for cancer development and metastasis (28)(29)(30). In addition, FAK can increase secretion of the matrix metalloproteinases in tumor cells, including MMP-2 and MMP-9 (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of FAK promotes the proliferation and invasion of tumor cells, which are crucial for cancer development and metastasis (28)(29)(30). In addition, FAK can increase secretion of the matrix metalloproteinases in tumor cells, including MMP-2 and MMP-9 (30,31). Therefore, the levels of the above proteins are significantly involving with the capabilities of malignant tumor cell invasion and metastasis through degradation of the extracellular matrix (ECM) (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…57 Recently, some studies provided mechanistic clues showing that BaP may contribute to lung cancer cell invasion and metastasis by upregulating proinflammatory chemokines (IL8, CCL-2, CCL-3) and the one of the master regulator of the epithelial-to-mesenchymal transition, Twist. 60 BaP treatment was also able to increase the metastatic potential of hepatocellular carcinoma cell lines in a mouse model, likely through an activation of both angiogenesis and NF-kB pathway. 60 BaP treatment was also able to increase the metastatic potential of hepatocellular carcinoma cell lines in a mouse model, likely through an activation of both angiogenesis and NF-kB pathway.…”
Section: Hallmark 6: Activating Invasion and Metastasismentioning
confidence: 92%
“…58,59 Moreover, BaP was able to induce cell migration in triple-negative breast cancer MDA-MB-231 cells through a lipoxygenase-and Src-dependent pathway, notably by increasing the secretion of metalloproteinase MMP-2 and MMP-9. 60 BaP treatment was also able to increase the metastatic potential of hepatocellular carcinoma cell lines in a mouse model, likely through an activation of both angiogenesis and NF-kB pathway. 51 In conclusion, BaP is able to promote cell migration and invasion, contributing to increase the metastatic potential of several epithelial cells in different experimental settings.…”
Section: Hallmark 6: Activating Invasion and Metastasismentioning
confidence: 92%